“Just to Jog My Memory”: An Examination of Forensic Interviewers’ Note-taking Behaviors and Perceptions of Notes With Child Witnesses - Williams, Shanna (Journal of interpersonal violence, 2024)
In the current study, we surveyed forensic interviewers (N = 137) on their note-taking practices, perceptions of note-taking, and note-taking training. Many forensic interviewers surveyed (81%) reported that they take notes during forensic interviews. Of those, the most common reason for note-taking was to assist with remembering what the interviewee reported during the interview (89%) and to guide the formulation of follow-up questions (87%). Note-taking style was also reported upon, with most respondents indicating that they write down keywords that may be used again in the interview (78%), as well as short utterances or sentences related to the presenting narrative (61%). Finally, the majority (50%) of respondents who take notes reported always taking notes, although 29% reported taking notes most of the time. Of those respondents who reported not taking notes during forensic interviews, the majority listed the reasons as being that it distracts the child from the interview (85%) and causes them to break eye contact with the child (46%). Overall, many respondents endorsed the benefits of note-taking to the interviewing process, whereas a small minority reported some perceived risks or concerns with note-taking during interviews. Perhaps most notably, forensic interviewers, both of whom take notes and those who do not, reported low rates of note-taking training and a desire for more information on note-taking practices within the field. These results underscore the need for further research and best practice guidelines regarding note-taking during forensic interviews.